2000
DOI: 10.1074/jbc.275.20.14809
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of the Catalytic Domain of Human Matrix Metalloproteinase 19

Abstract: We have recently cloned MMP-19, a novel matrix metalloproteinase, which, due to unique structural features, was proposed to represent the first member of a new MMP subfamily (Pendá s, A. M., Knä uper, V., Puente, X. S., Llano, E., Mattei, M. G., Apte, S., Murphy, G., and Ló pez-Otin, C. -Pro-Leu-Gly-Dpa-Ala-Arg-NH 2 and, with higher efficiency, the stromelysin substrate McaPro-Leu-Ala-Nva-Dpa-Ala-Arg-NH 2 . Kinetic analysis of the interactions of the catalytic domain of MMP-19 with the natural MMP inhibitors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
107
0
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(110 citation statements)
references
References 47 publications
0
107
0
3
Order By: Relevance
“…38 MMP-2, also previously known as the Type IV collagenase, 39 had substrate specificity to denature collagens, Type V, VII, X, XII collagens, vitronectin, aggrecan, galectin-3, and elastin, and most of them were also identified. Various substrates of MMP-19 have been identified in vitro 40 , including type IV collagen, gelatin, laminin-1, nidogen 1, fibronectin, and tenascin-C, which were also mostly detected. The identification of these bone-specific proteins demonstrated the effective of the sequential protein extraction protocol developed in this study.…”
Section: D-lc-msmentioning
confidence: 99%
“…38 MMP-2, also previously known as the Type IV collagenase, 39 had substrate specificity to denature collagens, Type V, VII, X, XII collagens, vitronectin, aggrecan, galectin-3, and elastin, and most of them were also identified. Various substrates of MMP-19 have been identified in vitro 40 , including type IV collagen, gelatin, laminin-1, nidogen 1, fibronectin, and tenascin-C, which were also mostly detected. The identification of these bone-specific proteins demonstrated the effective of the sequential protein extraction protocol developed in this study.…”
Section: D-lc-msmentioning
confidence: 99%
“…Accordingly, an in vivo study by Betsuyaku et al have suggested that neutrophil emigration in LPS-injured lungs occurs in MMP9-deficient mice, and that this molecule is thus not necessary for the neutrophils to cross the basement membrane (56). Pathophysiological differences existing between lung IR injury and LPS-induced lung injury, non-identified compensatory mechanisms of MMP9-deficient mice, and the involvement of other MMPs, like MMP2, membrane-type-MMP or the recently characterized MMP19, thought to play a significant role for basement membrane disruption (57), may account for the apparent discrepancy between the various experimental studies.…”
Section: Discussionmentioning
confidence: 99%
“…3,8 In vitro, MMP-19 is able to degrade many important BM components, e.g., type IV collagen, laminin-1, nidogen, fibronectin, tenascin-C isoform, aggrecan, type I gelatin and cartilage oligomeric matrix protein, 9 but does not activate any other latent MMPs. 10 By Northern hybridization, MMP-19 was originally detected in placenta, lung, pancreas, liver, ovary, spleen and intestine. 7 Independently, it was isolated as an autoantigen from the inflamed synovium of a patient suffering from rheumatoid arthritis.…”
mentioning
confidence: 99%
“…11,13 Because of its appearance in normal tissues, it is possible that MMP-19 is important in normal tissue remodeling or activation of secreted and membrane-bound proteins, like growth factors. 10 Our aim was to determine whether MMP-19 is induced in the epithelium during remodeling associated with either wound repair or cancer invasion. We show here that MMP-19 can be expressed by proliferating, but not migrating, keratinocytes; is upregulated by TNF-␣ and PMA in keratinocyte cultures; and, unlike several classical MMPs, disappears from proliferating keratinocytes during neoplastic dedifferentiation.…”
mentioning
confidence: 99%